Alpinetin Attenuates Persistent Inflammation, Immune Suppression, and Catabolism Syndrome in a Septic Mouse Model. (5th July 2021) - Liu, Yukun; Wang, Kang; Feng, Qaunrui; Zhang, Yongsheng; Wang, Chuntao; Liu, Qinxin; Liu, Xinghua; Wang, Xiang; Gao, Wei; Bai, Xiangjun; Li, Zhanfei; Wang, Yuchang
Abstract : Patients who survive the acute phase of sepsis can progress to persistent inflammation, immunosuppression, and catabolism syndrome (PICS), which usually results in extended recovery periods and multiple complications. Alpinetin is a flavonoid isolated from Alpinia katsumadai Hayata that has been demonstrated to have anti-inflammatory, antibacterial, and antioxidant activities. The aim of this study was to investigate whether the administration of alpinetin could attenuate PICS in a septic mouse model. Mice were randomly divided into four groups: the (1) sham-operated group, (2) sham+alpinetin (1 mg/kg intravenously infused for once per day after sham operation), (3) cecal ligation and puncture (CLP), and (4) CLP+alpinetin (50 mg/kg intravenously infused for once per day after CLP). Eight days after sham operation or CLP surgery, mice were euthanized for subsequent examination. Alpinetin significantly improved the survival of septic mice. Also, it attenuated the CLP-induced persistent inflammation, immunosuppression, and catabolism syndrome. The level of plasma proinflammatory cytokines and apoptosis of T lymphocytes were obviously decreased by alpinetin as well. Moreover, oxidative stress in the organs was compelling lower in the alpinetin-treated CLP mice. In this clinically relevant model of sepsis, alpinetin ameliorates CLP-induced organ dysfunction and improves the likelihood of survival, possibly through suppressing the inflammatory response, oxidative stress, and apoptosis. These findings suggested that alpinetin could be a potential novel therapeutic approach to prevent sepsis-induced PICS.